Odpowiedzi

2010-04-12T21:59:37+02:00
A4x-3x=5+3 x=8
b2x=5/2 x=2,5
c 3x=3/3 x=1
d -6x=30 /(-6) x=-5
e -10x=-13/(-10) x=1,3
f -2x=2/(-2) x=-1
Najlepsza Odpowiedź!
2010-04-12T22:07:10+02:00
A) 4x - 3 = 3x + 5 |+3
4x=3x+8 |-3x
x=8
b) 5x + 2 = 7 - 3x |+3x
8x +2 = 7 |-2
8x = 5 |:8
x=5/8
c) 3 ( x - 1 ) = 0 |:3
x-1=0
x=1
d) -6 ( x + 1 ) = 24 |:(-6)
x+1=-4
e) -7 ( x - 2 ) = 3x - 1
-7x +14 = 3x-1 |+7x
14=10x -1 |+1
15=10x |:10
x=1,5
f) 4 ( x - 1 ) = 6 ( 1 + x )
4x-4=6+6x |-4x
-4=6+2x |-6
-10 = 2x |:2
x=-5